Climate change shifts agropastoral-pastoral margins in Africa putting food security and livelihoods at risk. (1st September 2022) - Nidumolu, Uday; Gobbett, David; Hayman, Peter; Howden, Mark; Dixon, John; Vrieling, Anton
Abstract: Climate is one of the key factors determining the suitability of land for agricultural production and influencing the spatial transition between grazing and cropping-dominated farming systems in Africa. We identified the climate indices that best align with the margin between the Agropastoral and Pastoral Farming Systems in the historical climate (1981–2006). We then used global climate model results to assess how these agropastoral-pastoral margins are likely to shift by 2050 as a consequence of forecasted climate change. We found that the agropastoral-pastoral margin will retreat across Africa resulting in less area climatically suited for productive agropastoral practices. Depending on the climate model, climate index and projections used, the conversion of land currently suitable for agropastoral production to land suitable for pastoral production across the continent leads to a reduction of the current 4.43 M km 2 of Agropastoral Farming Systems to between 1.2 M km 2 and 3.6 M km 2 . This reduction of 27%–81% of the Agropastoral zone would threaten food security and livelihoods in those areas. While we did not assess this aspect, the retreat of the agropastoral-pastoral margin may be offset by the conversion of higher rainfall zones to suitability for agropastoral production which would expand the area suitable for the Agropastoral Farming System. Identifying the locations and vulnerability to the climatic shifts along agropastoral-pastoral margins can help policy makers and planners to define strategies for improving the long-term resilience of livelihoods to climate change.